THE EFFECT OF THE QUIZ TEAM METHOD IN THE DISCOVERY LEARNING MODELS OF THE LEARNING OUTCOMES OF THE STUDENTS - Riswandi, Riswandi; Auliah, Army; Jusniar, Jusniar (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
This quasi-experimental study aims to determine the effect of the Quiz Team Method in the Discovery Learning Model on the learning outcomes of students of class XI MIPA SMA Negeri 7 Takalar on the buffer solution material. The posttest only control group design was carried out on class XI SMA Negeri 7 Takalar successively as the experimental class and the control class which was determined by random sampling from class XI MIPA SMA Negeri 7 Takalar as the population. This study uses descriptive analysis and inferential analysis. The results of the descriptive analysis obtained that the average learning outcomes of the experimental group were 78.9 higher than the control group, which was 76.70. The results of inferential statistical analysis on student learning outcomes showed that the experimental group and control group data came from a homogeneous population Fcount 1.59 < Ftable 1.78 but not normally distributed so that the hypothesis test used was a non-parametric statistical test, Mann-Whitney with = 0.05 obtained Zcount>Ztable (2.08>1.64). So it can be concluded that there is an effect of the Quiz Team method in the Discovery Learning model on the learning outcomes of class XI MIPA students at SMA Negeri 7 Takalar on the buffer solution material.